TAFSIR AYAT – AYAT DAKWAH - Kusnadi Kusnadi (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2020)
The word da'wah is a term that is quite popular in Islamic scholarship. Da'wah is also a word that has many synonym variants whose substance is generally the same but has different implications. In the study of da'wah science, the term "da'wah" is distinguished from "dakwah science". Da'wah is generally defined as an activity calling or inviting other people to do good. While the science of da'wah is defined as a science that studies the ins and outs of da'wah activities starting from the input, process to output or the results of the da'wah carried out as well as all studies related to the scientific development of da'wah. This paper is the scope of the ontology of da'wah, because the scope of its study is the aspect of what da'wah is, which will describe the various variants of the term da'wah in the al-Qur'an and attempt to explore several synonyms of da'wah, words that have correlation and substance with the term da'wah. Then at the end of the discussion will highlight the implications of preaching in the contemporary era, the digital era in which there are opportunities and challenges of preaching.